Clinical manifestations and basic mechanisms of myocardial ischemia/reperfusion injury - Chiu-Fen Yang (Tzu-Chi Medical Journal, 2018)
Acute myocardial ischemia/reperfusion (I/R) injury is a significant, unsolved clinical puzzle. In the disease context of acute myocardial infarction, reperfusion remains the only effective strategy to salvage ischemic myocardium, but it also causes additional damage. Myocardial I/R injury is composed of four types of damage, and these events attenuate the benefits of reperfusion therapy. Thus, inventing new strategies to conquer I/R injury is an unmet clinical need. A variety of pathological processes and mediators, including changes in the pH, generation of reactive oxygen radicals, and intracellular calcium overload, are proposed to be crucial in I/R-related cell injury. Among the intracellular events that occur during I/R, we stress the importance of protein phosphorylation signaling and elaborate its regulation. A variety of protein kinase pathways could be activated in I/R, including reperfusion injury salvage kinase and survivor-activating factor enhancement pathways, which are critical to cardiomyocyte survival. In addition to serine/threonine phosphorylation signaling, protein tyrosine phosphorylation is also critical in multiple cell functions and survival. However, the roles of protein kinases and phosphatases in I/R have not been extensively studied yet. By better understanding the mechanisms of I/R injury, we may have a better chance to develop new strategies for I/R injury and apply them in the clinical patient care.